"An Empire for Liberty": Reassessing US Presidential Foreign Policy Rhetoric. Issue 4 (2nd October 2022) - Prasch, Allison M.; Stuckey, Mary E.
ABSTRACT: Empire is central to US foreign policy aims but is rarely taken directly into account in studies of American presidential foreign policy rhetoric. We argue here that in doing such studies, analytic attention should be paid to questions of empire as foundational to the development of the United States and to articulations of the American nation. We examine two historical and two heuristic categories used to understand US presidential foreign policy discourse and argue for refocusing analysis by placing questions of whiteness, empire, and colonialism at the core of those categories.